Management of societal value creation through “creating shared value” : Making corporate sustainability more systematic - Kallio, Jarno (My University, 2021)
This thesis was conducted as an assignment for a multinational technology corporation (“the Firm”) headquartered in Finland. The objective of this constructive research was to systematize the Firm’s sustainability strategy by developing a tailored solution for managing societal value creation. Additionally, theoretical understanding of corporate sustainability was refined. Corporate sustainability can no longer be regarded as an optional endeavour due to immense stakeholder pressure. In general, managers have recognized this issue, but they are poorly equipped to implement such aspirations systematically. Literature on corporate sustainability is also disharmonious, boasting a multitude of overlapping concepts with vague definitions and disputed characteristics. Accordingly, this thesis aims to tie up the loose ends in both theoretical and managerial domains of corporate sustainability by drawing on the concept of creating shared value (CSV). Systematization of corporate sustainability is studied with a pragmatic orientation in the context of for-profit organizations. Firstly, the meaning of CSV for business is elaborated. Secondly, contemporary operationalization methods of CSV are synthesized. Lastly, a new framework for managing societal value creation is constructed which aims to solve the Firm’s problem of fragmented sustainability practices. The construction was grounded in a diversified literature review and tailored according to empirical findings on the Firm’s context. This data was collected with standardized open-ended interviews and extracted perceptions were compared with official documents. Finally, the resulting construct was validated by subjecting it to a weak market test to Firm executives. The theoretical contribution was based on a refined conception of CSV. Its original definition was accepted but it was supplemented with enhanced definitional demarcation, role of firms, role of CSV in society, and analytical rigour. Managerial contribution centred on breaking down the complexity related to societal value creation initiatives. Due to being an intensive qualitative study, the theoretical contribution can be generalized analytically whereas the managerial contribution may be generalizable on a case-to-case basis to other firms in similar contexts. Promising avenues for future research were identified especially in terms of internally coherent sustainability performance measurement systems.

Tämä konstruktiivinen tutkimus toteutettiin toimeksiantona suomalaiselle teknologiateollisuuden yritykselle (“Yritys”), jolla on myös toimintaa kansainvälisesti. Tavoitteena oli systematisoida Yrityksen vastuullisuuskäytäntöjä yhteiskunnallisen arvonluonnin kontekstissa ja tuottaa tähän räätälöity prosessi. Lisäksi tutkimus pyrki edistämään teoreettista ymmärrystä vastuullisesta liiketoiminnasta ja kehittämään sen jalkauttamiskäytäntöjä. Kasvavan institutionaalisen paineen takia vastuullisen liiketoiminnan harjoittamisesta on tullut yrityksille pakollista toimintaedellytysten turvaamiseksi. Yritysjohtajat tunnistavat tämän tilanteen, mutta heillä ei tyypillisesti ole asianmukaista ymmärrystä tai menetelmiä vastuullisuuden jalkauttamiseen. Kirjallisuudessa on myös runsaasti erimielisyyksiä vastuullisuuskäsitteistä ja niiden merkityksistä. Tämä tutkimus kuroo umpeen nykytietämyksen aukkokohtia hyödyntämällä jaetun arvonluonnin käsitettä (creating shared value eli CSV). Vastuullisuustoiminnan systematisointi rajataan voittoa tavoitteleviin organisaatioihin ja sitä lähestytään pragmaattisesti seuraavilla tutkimuskysymyksillä: 1) mitä jaettu arvonluonti merkitsee liiketoiminnalle, 2) millaisia jaetun arvonluonnin operationalisointikeinoja on nykykirjallisuudessa ja 3) millainen viitekehys Yritykselle tulisi kehittää yhteiskunnallisen arvonluonnin johtamiseen. Ratkaisun rakentaminen perustui monialaiseen kirjallisuuskatsaukseen ja se räätälöitiin Yrityksen nykytilan ja tarpeiden mukaan. Empiirinen aineisto kerättiin puolistrukturoiduilla haastatteluilla ja vertaamalla näitä havaintoja Yrityksen virallisiin asiakirjoihin. Konstruktiolle suoritettiin lopuksi heikko markkinatesti haastattelemalla Yrityksen johtohenkilöitä. Tutkimuksen teoreettinen kontribuutio perustui CSV-käsitteen jalostamiseen. Sen alkuperäinen määritelmä hyväksyttiin, mutta sitä täydennettiin selkeämmällä rajauksella, CSV:tä käyttävien yritysten roolilla, CSV:n yhteiskunnallisella roolilla sekä analyyttisyydellä. Liikkeenjohdollinen kontribuutio keskittyi yhteiskunnallisen arvonluonnin kompleksisuuden purkamiseen. Koska kyseessä oli intensiivinen kvalitatiivinen tutkimus, voidaan teoreettinen kontribuutio yleistää analyyttisesti ja liikkeenjohdollinen kontribuutio voitaneen yleistää case-to-case –periaatteella muihin yrityksiin samankaltaisissa konteksteissa. Mahdollisuudet tuleville tutkimuksille ovat lupaavia etenkin aiempaa johdonmukaisempien vastuullisuussuorituskykyä mittaavien järjestelmien kehittämisessä.
Keywords: creating shared value, corporate sustainability, societal value creation